The management of pseudomyogenic hemangioendothelioma of the foot: A case report and review of the literature. Issue 6 (21st September 2018) - Pranteda, Guglielmo; Magri, Francesca; Muscianese, Marta; Pigliacelli, Flavia; D'Arino, Andrea; Federico, Alessandro; Pranteda, Giulia; Bartolazzi, Armando
Abstract: Pseudomyogenic hemangioendothelioma (PMH) is a rare, mostly indolent, endothelial neoplasm of low‐grade malignancy, often mimicking myoid and epithelioid tumors histologically. It is more frequent in young adult males and it usually presents with multiple cutaneous nodules, mostly localized at the extremities. It traverses several tissue planes simultaneously and can involve dermis, subcutis, skeletal muscle, and bone. Histologically, it is characterized by plump spindle cells with eosinophilic cytoplasm, often arranged in fascicles and epithelioid cells with "pseudomyogenic" morphology. Immunohistochemically, PMH is positive for Factor VIII, FLI‐1, INI‐1, vimentin, MDM2, CDK4, CD31, AE1/AE3, EMA, and P63. The efficacy of treatments is only partially known. Because of the frequent multifocal aspect of PMH, which contraindicates surgery, systemic treatments, such as gemcitabine, sirolimus, and everolimus are used. Based on our observation of multifocal PMH of the foot in a 17‐year‐old male patient, treated with gemcitabine with complete cutaneous response in a 2‐year follow‐up, we decided to discuss this rare tumor and underline its progression and therapeutic approaches. Thanks to a correct diagnosis, it is possible to avoid aggressive therapeutic approaches, which would be necessary for nonindolent diseases, such as sarcoma, which often needs amputation.